Social Inclusion Drives Business Sales: A Literature Review on the Case of the Employment of Persons With Disabilities - Boris Miethlich; Anett G. Oldenburg (33nd International Business Information Management Association Conference (IBIMA), Education Excellence and Innovation Management through Vision 2020, Granada, Spain, 10-11.04.2019, 2019)
So far companies seem to ignore the potential of persons with disabilities (PWD) as customers and as employees. Although there is some empirical evidence that PWD employment can bring many benefits to companies and that social inclusion can attract a lasting customer base. The employment of PWD and social inclusion, generally, are important social commitments of companies and should represent a central element of the Corporate Social Responsibility (CSR) strategy. CSR is also an interesting marketing instrument for differentiation. However, customers are more aware of productrelated CSR activities than philanthropy or sustainable business initiatives. The aim of this article is to analyze how the promotion of social inclusion, through the example of the employment of PWD, could impact directly or indirectly on business sales. The research is based on a literature review. The selected literature was evaluated regarding the impact on business sales using a deductive content analysis. The results show that social inclusion, as a CSR activity, contributes to increased sales. This is particularly important when it comes to providing services and direct customer contact. Through social inclusion, the company reflects the diversity of existing and potential customers. In this way, new customers can be acquired, customer loyalty promoted or strengthened, and, as a result, sales increased. CSR activities that are used as a marketing tool for differentiation and do not pursue the sole goal of strengthening the company's reputation can create a competitive advantage and thus secure market share, open-up new market segments and permanently increase sales.
Keywords: J14; M14; I18; 330; social inclusion; disability management; persons with disabilities; CSR